Low-molecular-weight hyaluronan (LMW-HA) accelerates lymph node metastasis of melanoma cells by inducing disruption of lymphatic intercellular adhesion. (1st November 2016) - Du, Yan; Cao, Manlin; Liu, Yiwen; He, Yiqing; Yang, Cuixia; Wu, Man; Zhang, Guoliang; Gao, Feng
ABSTRACT: Endothelial integrity defects initiate lymphatic metastasis of tumor cells. Low-molecular-weight hyaluronan (LMW-HA) derived from plasma and interstitial fluid was reported to be associated with tumor lymphatic metastasis. In addition, LMW-HA was proved to disrupt lymphatic vessel endothelium integrity, thus promoting lymphatic metastasis of tumor cells. Until now, there are few reports on how LMW-HA modulates lymphatic endothelial cells adhesion junctions and affects cancer cells metastasizing into lymph vessels. The aim of our study is to unravel the novel mechanism of LMW-HA in mediating tumor lymphatic metastasis. Here, we employed a melanoma metastasis model to investigate whether LMW-HA facilitates tumor cells transferring from foci to remote lymph nodes by disrupting the lymphatic endothelial integrity. Our data indicate that LMW-HA significantly induces metastasis of melanoma cells to lymph nodes and accelerates interstitial-lymphatic flow in vivo . Further experiments show that increased migration of melanoma cells across human dermal lymphatic endothelial cell (HDLEC) monolayers is accompanied by impaired lymphatic endothelial barrier function and increased permeability. The mechanism study reveals that VE-cadherin-β-catenin pathway and relevant signals are involved in modulating the interactions between endothelial cells and that a significant inhibition of lymphatic endothelium disruption is observed when antibodies to the LMW-HA receptor (LYVE-1) are present. Thus, our findings demonstrate a disruptive effect of LMW-HA on lymphatic endothelium continuity which leads to a promotion on melanoma lymphatic metastasis and also suggest a cellular signaling mechanism associated with VE-cadherin-mediated lymphatic intercellular junctions.